Crystallite size and phase purity in Pb1-xSrxTiO3 ferroelectric perovskites for biomedical applications via controlled sintering - Rahmat Doni Widodo; Samsudin Anis; Deni Fajar Fitriyana; Maykel Manawan; Joni Sah; Aji Santiko; Rizalman Bin Mamat; Abdulfatah Abdu Yusuf; Muhammad Imam Ammarullah (Journal of Asian Ceramic Societies)
Lead strontium titanate (Pb1-xSrx)TiO3 (PST) is a ferroelectric perovskite material with tunable properties, including Curie temperature, spontaneous polarization, and high dielectric permittivity, making it promising for advanced biomedical applications, such as biosensors, bioimaging, and light-activated therapeutics. This study investigates the effect of varying sintering temperatures on the crystallite size and phase purity of PST, aiming to optimize its performance for biomedical devices. PbCO3, SrCO3, and TiO2 powders were processed via ball milling for 58 hours, followed by sintering at temperatures ranging from 500°C to 1100°C. Laser diffraction particle size analysis and X-ray diffraction (XRD) were used to assess the particle size and crystal phase transformations. The results demonstrate that higher sintering temperatures improve the PST phase composition, reducing impurities and enhancing crystallite growth. The most significant crystal growth was observed at 900°C, while the optimal phase purity and crystallite size (91.5 nm) were achieved at 1100°C, producing 100% single-phase PST. These findings emphasize the critical role of sintering temperature in tailoring PST’s properties, enhancing its suitability for electronic and microelectronic biomedical devices. Controlled sintering in perovskite materials opens new pathways for their application in medical diagnostics and therapeutic technologies.